Contrastive analysis of sterotypical humor found in the characters donkey and burro in the movie shrek (2001). A localized proposal of humor rendering techniques. - Cotapo Burgos, Edilma Maritza (2016)
This research document attempts to create awareness on the fact that as the industry of entertainment grows, the need for reaching vast amounts of viewers for these cinematographic productions is imperative. Thus, it becomes important for translators to find the means to convey the message of these productions in spite of language and cultural barriers. Every production represents a challenge for translators, but there are some genres that are more complex than other as is the case of humor. There are several problems that translator can face when translating humor, for instance: idiomatic expression, cultural references, words, ideas, places, objects that might not exist in the target culture and/or language becoming into the so called cultural untranslatability. This paper, provides samples of the most common problems when translating humor as well as techniques that shade some light on the problem of translating humor. To come up with techniques a research was made about stereotypes in American and Latin-American culture taking as a reference the animated film Shrek (2001). A localized translation for Ecuadorians was rendered and a survey was applied to seventy-five people in order to corroborate the hypothesis. The results of the survey as well as the analysis could prove that the when translating humor, it is mandatory to go through an adaptation process to achieve success. This means that it is possible to gain the acceptance of the audience by providing a good rendering via the study of the target culture and the application of the correct techniques.